2018
DOI: 10.1007/s12275-018-7449-0
|View full text |Cite
|
Sign up to set email alerts
|

Colistin resistance in Enterobacter spp. isolates in Korea

Abstract: We investigated the colistin resistance rate among 356 Enterobacter spp. clinical isolates from eight hospitals in Korea. Antibiotic susceptibility testing was performed by broth microdilution. While 51 of 213 (23.9%) Enterobacter cloacae isolates were colistin-resistant, only six of 143 (4.2%) E. aerogenes isolates showed resistance. We also identified the skip well phenotype in eight E. cloacae and three E. aerogenes isolates. Multilocus sequence typing for E. cloacae and randomly amplified polymorphic DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…However, the appearance of colistin-resistant strains has risen dramatically in the last decade due to antibiotic pressure in both human treatment and its use in agriculture (Kempf et al, 2016 ; Olaitan et al, 2016 ). In a recently published study (Hong et al, 2018 ), the in vitro activity of colistin was analyzed against 356 clinical strains of Enterobacter spp. from eight Korean hospitals, founding that 23.9 and 4.2% of E. cloacae and E. aerogenes strains, respectively, were resistant to colistin.…”
Section: Introductionmentioning
confidence: 99%
“…However, the appearance of colistin-resistant strains has risen dramatically in the last decade due to antibiotic pressure in both human treatment and its use in agriculture (Kempf et al, 2016 ; Olaitan et al, 2016 ). In a recently published study (Hong et al, 2018 ), the in vitro activity of colistin was analyzed against 356 clinical strains of Enterobacter spp. from eight Korean hospitals, founding that 23.9 and 4.2% of E. cloacae and E. aerogenes strains, respectively, were resistant to colistin.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among 6 colistin-resistant E. aerogenes isolates; meropenem, cefepime, gentamicin, ciprofloxacin, ceftazidime and trimethoprim/sulfomethoxazole resistant rates were 16.7% (1 isolate), 16.7% (1 isolate), 50%(3 isolates), 50%(3 isolates), 83.3%(5 isolates) and 83.3%(5 isolates), respectively. 1 In two articles published in 2016, researchers reported that colistin has failed in some treatments due to colistin resistance; E.cloacae and E.aerogenes species as opportunistic pathogens that can cause serious problems for human health. 22,23 In a study conducted in Brazil in 2018, the researchers evaluated the resistance profiles of 14 Enterobacter isolates ( 8 E.cloacae and 6 E.aerogenes) to different antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…These facultative anaerobe Gram negative rods may cause opportunistic infections especially in immunocompromised patients. 1 Hoffman et al described E.cloacae, E.asburiae, E.hormaechei and E.kobei species as ''E.cloacae complex'' in 2005. [2][3][4][5] Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanni, Pseudomonas aeruginosa ve Enterobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…The carbapenemase genes bla KPC , bla IMP , bla VIM , bla NDM , bla SPM , and bla SIM and an extended spectrum β-lactamase gene bla CTX-M were detected by PCR amplification and Sanger sequencing using previously described primers [ 18 , 19 , 20 ]. The presence of mcr , a plasmid-borne colistin resistance gene, was also determined by PCR [ 21 ].…”
Section: Methodsmentioning
confidence: 99%